THE PARTIAL MOLAR VOLUME AND THERMAL EXPANSIVITY OF TIO2 IN ALKALI SILICATE MELTS: SYSTEMATIC VARIATION WITH TI COORDINATION - Liu Q.; Lange R.A. (My University, 2001)
The densities of seven K2O-TiO2-SiO2 (KTS) liquids and seven Na2O-TiO2-SiO2 (NTS) liquids have been measured between 1236 and 1771 K using the double-bob Archimedean method. In addition, the low-temperature density of these liquids at their limiting fictive temperature (T'f; near the glass transition) were also measured. Compositions range from 15 to 39 mol % K2O and Na2O, 10 to 35 mol % TiO2, and 33 to 61 mol % SiO2. Plots of molar volume vs. temperature are linear for all samples in the stable liquid region, but there is an increase in the slope (#V/#T) with decreasing temperature in the supercooled liquid region, analogous to that observed for the heat capacity of similar alkali titanosilicate liquids. Derived values of VTiO2 (at 1373 K) decrease systematically from 32.5 to 26.5 cm3/mol between 39 and 15 mol% K2O and from 29.6 to 25.7 cm3/mol between 39 and 25 mol% Na2O (and are nearly constant at ~25 +/- 0.5 cm3/mol between 25 and 15 mol% Na2O). Values of VTiO2 do not appear to be a function of the TiO2 concentration, but instead depend strongly on the nature of the alkali present (larger by ~3 cm3/mol in KTS vs. NTS liquids) and the degree of polymerization (increase with NBO/T). By comparing our values of VTiO2 at 1373 K to published Ti coordination numbers on samples of similar composition, we calculate that the average Ti coordination number varies from ~4.0 to 5.1 in the KTS liquids and from ~4.6 to 5.5 in the NTS liquids. The value of #VTiO2#T in the stable liquid region correlates strongly with VTiO2 at 1373 K (and therefore with Ti coordination). It is near zero when the average coordination is close to four, but reaches a maximum of ~6 to 8 x 10-3 cm3/mol-K when the average Ti coordination number is close to five. In all corresponding glasses, the value of #VTiO2#T is zero. Together, these features require that #VTiO2#T in the liquid is associated with the presence of [5]Ti and involves structural changes not available to solids.